Radiofrequency identification and medical devices: the regulatory framework on electromagnetic compatibility. Part II: active implantable medical devices. (May 2012) - Mattei, Eugenio; Censi, Federica; Triventi, Michele; Bartolini, Pietro; Calcagnini, Giovanni
The number and the types of electromagnetic emitters to which patients with active implantable medical devices (AIMD) are exposed to in their daily activities have proliferated over the last decade. Radiofrequency identification (RFID) is an example of wireless technology applied in many fields. The interaction between RFID emitters and AIMD is an important issue for patients, industry and regulators, because of the risks associated with such interactions. The different AIMDs refer to different standards that address the electromagnetic immunity issue in different ways. Indeed, different test setups, immunity levels and rationales are used to guarantee that AIMDs are immune to electromagnetic nonionizing radiation. In this article, the regulatory framework concerning electromagnetic compatibility between RFID systems and AIMDs is analyzed to understand whether and how the application of the current AIMD standards allows for the effective control of the possible risks associated with RFID technology.